2011
DOI: 10.1091/mbc.e11-09-0778
|View full text |Cite
|
Sign up to set email alerts
|

The Cx26-G45E mutation displays increased hemichannel activity in a mouse model of the lethal form of keratitis-ichthyosis-deafness syndrome

Abstract: Dominant Cx26 mutations that cause keratitis-ichthyosis-deafness syndrome (KIDS) show increased hemichannel activity. Transgenic expression of these mutations recapitulates human skin disease in mice. Excess hemichannel activity persists in diseased epidermis from the transgenic mice. Thus hemichannel activity may be a novel therapeutic target in the treatment of KIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 72 publications
5
108
0
Order By: Relevance
“…Connexin hemichannels have long been considered as merely structural precursors, yet compelling evidence in the last few years clearly shows that hemichannels autonomously form a pathway of communication, albeit not between neighboring cells, as is the case for gap junctions, but between the cytosol of individual cells and their extracellular environment. In fact, not only dysregulated gap junctional communication, but also aberrant connexin hemichannel activity has been observed in a number of skin diseases [28][29][30][31]. Several authors have reported Cx43 modulation in human diseases related to poor skin healing, such as hypertrophic scars and keloids [11] or in wounds of diabetic patients [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Connexin hemichannels have long been considered as merely structural precursors, yet compelling evidence in the last few years clearly shows that hemichannels autonomously form a pathway of communication, albeit not between neighboring cells, as is the case for gap junctions, but between the cytosol of individual cells and their extracellular environment. In fact, not only dysregulated gap junctional communication, but also aberrant connexin hemichannel activity has been observed in a number of skin diseases [28][29][30][31]. Several authors have reported Cx43 modulation in human diseases related to poor skin healing, such as hypertrophic scars and keloids [11] or in wounds of diabetic patients [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Communication deficient HeLa cells were plated on 22-mm 2 coverslips, grown to 50% confluence, and transiently transfected with wild-type Cx26, Cx26-D50A, or Cx26-A88V in pIRES2-EGFP2 using Lipofectamine 2000 (Invitrogen, Carlsbad, CA) as previously described (29,30) with the exception that calcium concentrations in the tissue culture media were elevated to a final concentration of 4 mM with supplemental CaCl 2. Primary human keratinocytes were obtained from the Living Skin Bank (Stony Brook University, Stony Brook, NY) and cultured in KGM-Gold keratinocyte growth medium (Lonza, Walkersville, MD).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain hemichannel current-voltage (I-V) curves, cells were initially clamped at Ϫ40 mV and subjected to 5-s depolarizing voltage steps ranging from Ϫ30 to ϩ60 mV in 10-mV increments (21). Electrophysiological measurements in transfected HeLa cells or primary human keratinocytes were carried out using whole cell patch clamp at room temperature as previously described (29,30). At the beginning of each experiment, cells were clamped at 0 mV and then stepped for 2-s intervals to different voltages (Ϫ110 to ϩ110 mV in 20-mV increments).…”
Section: Methodsmentioning
confidence: 99%
“…Cx30 forms voltage-gated hemichannels (Valiunas and Weingart, 2000), which are normally closed under physiological conditions and open in response to low extracellular concentrations of Ca 2+ and Mg 2+ (De Vuyst et al, 2007;Tong et al, 2007;Verselis and Srinivas, 2008). Importantly, leaky hemichannels that result in cell death have been reported for a number of other connexin mutations (Gerido et al, 2007;Lee et al, 2009;Mese et al, 2011;Stong et al, 2006) and also for the A88V Cx26 mutation, which is linked to KID syndrome (Mhaske et al, 2013). The crystal structure of Cx26 suggests that part of the…”
Section: The A88v Mutant Linked To Clouston Syndromementioning
confidence: 99%